Relationship between sperm motility, morphology and the fertility of stallions - Love, C.C (Theriogenology, 2011)
Sperm quality has an important role in determining fertility. Although there have been numerous studies to document the relationship between sperm quality and fertility, the methods of determining this association and conclusions vary. In the present study, computer-assisted sperm analysis (CASA) was used for evaluation of sperm motility, and differential interference contrast (DIC) microscopy was used for evaluating sperm morphologic features of breeding stallions. Fertility was measured using three endpoints: seasonal pregnancy rate (PR), percent pregnant/cycle (PC), and percent pregnant/first cycle (FCP). Increased total sperm motility (P = 0.08) and progressive path velocity (P = 0.06) tended to be associated with higher PR, whereas percent coiled tails (P = 0.02) was associated with a lower PR. Sperm motility variables associated with an increase in PC and FCP included total, progressive, and rapid sperm motility, and increased path and progressive velocity. Percent pregnant/first cycle was the only fertility measure able to discriminate among high, average, and low fertility groups, based on total and progressive sperm motility. Percent normal sperm was the only morphology variable associated with an increased PC and FCP, whereas increased levels of most sperm morphologic abnormalities (including abnormal and detached heads, proximal and distal droplets, general midpiece abnormality, and coiled tails) were associated with a decline in PC and FCP. Sperm quality variables most highly correlated with fertility included percent total sperm motility (PR, r = 0.37, P < 0.05; PC, r = 0.59, P < 0.05; and FCP, r = 0.64, P < 0.05), and percent morphologically normal sperm (PC, r = 0.42, P < 0.05; and FCP, r = 0.39, P < 0.05).